2020
DOI: 10.1016/j.hrthm.2020.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocardiographic monitoring of patients with Coronavirus Disease 2019

Abstract: BACKGROUND Many of the drugs being used in the treatment of the ongoing pandemic coronavirus disease 2019 (COVID-19) are associated with QT prolongation. Expert guidance supports electrocardiographic (ECG) monitoring to optimize patient safety.OBJECTIVE The purpose of this study was to establish an enhanced process for ECG monitoring of patients being treated for COVID-19.METHODS We created a Situation Background Assessment Recommendation tool identifying the indication for ECGs in patients with COVID-19 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
3
39
0
1
Order By: Relevance
“…The use of hydroxychloroquine (or chloroquine), azithromycin, and antiviral drugs could cause prolongation of the QT interval with an increased risk of arrhythmias. We observed cQT prolongation in 5 patients (17%), similar to a previous study, 5 but no sustained ventricular tachycardias were observed.…”
supporting
confidence: 90%
“…The use of hydroxychloroquine (or chloroquine), azithromycin, and antiviral drugs could cause prolongation of the QT interval with an increased risk of arrhythmias. We observed cQT prolongation in 5 patients (17%), similar to a previous study, 5 but no sustained ventricular tachycardias were observed.…”
supporting
confidence: 90%
“…Previous studies with extremely prolonged basal QT intervals may not reflect the patient’s real-world baseline repolarization status. These data have been replicated recently by the group from Yale 16 , that describe a significantly prolonged QTc interval after treatment among patients admitted to ICU after reviewing more than two thousands ECGs of patients with COVID-19; on the other hand, previous studies focus mostly on American population 12 15 , with lack of large series in other regions. A single European work showed a significantly prolonged QT interval in more than 20% of the sample 17 , but in this case patients were treated with chloroquine, which is known to affect QT interval in a greater degree than HCQ.…”
Section: Discussionmentioning
confidence: 74%
“…(103/524) of patients with COVID-19 had prolonged QTc interval and were more likely to be admitted to the ICU (Jain et al, 2020). Drugs for treating COVID-19 were regarded as the main cause of QTc prolongation, and this effect may be amplified when multiple QT-prolonging drugs were used in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Although QTc prolongation was more common in the ICU group (34.8% vs. 8.9%), there was no significant difference in values between the two groups in our cohort ( p = .184). Jain S et al reported that 19.7% (103/524) of patients with COVID‐19 had prolonged QTc interval and were more likely to be admitted to the ICU (Jain et al, 2020). Drugs for treating COVID‐19 were regarded as the main cause of QTc prolongation, and this effect may be amplified when multiple QT‐prolonging drugs were used in combination.…”
Section: Discussionmentioning
confidence: 99%